Environmental Impacts Evaluation of Sorbitol Production from Glucose - Rifkah Akmalina (Eksergi, 2019)
A life cycle assessment (LCA) has been performed on sorbitol production from glucose, which aims to quantify and evaluate the environmental impacts that produced from the process. SuperPro Designer software was employed to perform the process simulation, while SimaPro was used to quantify the LCA.Potency of global warming, acidification, eutrophication, photochemical oxidants creation, abiotic depletion, and ozone layer depletion were evaluated. A gate-to-gate LCA study of sorbitol production showed that global warming potential (GWP) had the largest impact to environment with the value of 3.551 kg CO2 eq/kg sorbitol. Glucose and electricity consumption were known as two major contributors to GWP, and hydrogen reactor was the main consumer of electricity. The use of glucose were responsible for more than 50% of total environmentalimpact in each category. Performing heat integration in sorbitol processing is highly recommended for gate-togate system to reduce energy demand, thus decreasing the environmental impacts. Therefore, this LCA study may be applied to perform a sustainable improvement on sorbitol production process.Keywords: sorbitol; life cycle assessment; global warming potential